Synthesis of fluorine-18-labeled losartan analogs as novel positron emission tomography tracers for cancer imaging - Pijeira, Martha Sahylí Ortega (2019)
Losartan is a selective antagonist of the angiotensin II type 1 receptor (AT1R). Several reports have highlighted the AT1R expression in several cancers enhancing tumor development and cancer progression. The aim of this thesis is the synthesis and evaluation of [18F]fluoroethyl-losartan ([18F]FEtLos) and [18F]ammoniomethyltrifluoroborate-losartan ([18F]AMBF3Los) as two novel losartan analogs to image AT1R-positive tumors using the positron emission tomography (PET). Initially, the cold compounds FEtLos and AMBF3Los were synthetized by alkylation and click chemistry reactions respectively, and characterized by spectroscopic techniques. Then, radiosynthesis of 2-[18F]fluoroethyl-tosylate was optimized from a radiation safety point of view. Next, [18F]FEtLos was manually synthetized by [18F]fluoroethylation of losartan with low molar activity and greater than 99% radiochemical purity. [18F]AMBF3Los was easily synthetized with greater than 97% radiochemical purity by one step 18F-19F isotopic exchange approach using low and high activities of [18F]fluoride that afforded molar activities ranging from 2 to 139 GBq/μmol. In vitro competition binding assays showed that FEtLos and AMBF3Los have low and high binding affinity to human AT1R, respectively. AT1R expression was confirmed in breast, ovarian and gastric derived-tumors implanted on Nude mice. In spite of the low affinity, [18F]FEtLos was specific for renal AT1R. However, [18F]FEtLos did not showed specificity for tumor AT1R binding. μPET imaging, autoradiography and ex vivo biodistribution studies showed the specificity of [18F]AMBF3Los for both kidney and tumor AT1R binding. However, [18F]AMBF3Los was not able to reach the tumor site once injected intravenously probably because of its rapid metabolism and very fast clearance. Nonetheless our results demonstrate that 18F-Angiotensin II Receptor Blockers (ARBs) derivatives could be suitable tracers to cancer imaging AT1R-expressing tumor microenvironment, however, radiolabeled ARBs that possess better pharmacokinetics profile may be required.